THE INFLUENCE OF EMPLOYEE DEVELOPMENT AND EMPOWERMENT OF HUMAN RESOURCES TO THE PERFORMANCE OF PENITENTIARY ORGANIZATIONS IN GREATER BANDUNG - Lilis Yuningsih (Universitas Pasundan, 2020)
The Low Performance of Penitentiary Organizations in Greater Bandung. The cause of the problem is allegedly Guidance for Employees and Empowerment of Human Resources has not been done on the Performance of Penitentiary Organizations in Greater Bandung. Human resources as part of the scope of Public Administration by using qualitative descriptive analysis research methods and quantitative analysis (path analysis), while the population is Bandung Correctional Institutions (Sukamiskin Class I Correctional Institution Bandung, Class IIA Banceuy Bandung and Class I Kebon Waru Bandung). Staff development and empowerment of human resources have been carried out in accordance with the capabilities of the apparatus at the Bandung Institute of Corrections. Simultaneously the effect of employee coaching and empowerment of human resources on the performance of the Bandung Correctional Institution in Greater Bandung was 69.9%, while the epsilon was 30.1%. Partial influence of employee coaching consisting of factors giving decent wages, providing opportunities and encouragement to develop careers, disciplining the rules to achieve high organizational effectiveness, The results of research indicate a new thing that Organizational Performance in Penitentiary in Greater Bandung needs make new breakthroughs so that employees can work more innovating into the future to produce employees who have high morale and fighting spirit in carrying out their duties. Meaning that it is necessary to optimize the development and empowerment of human resources towards the performance of organizations in Bandung Correctional Institutions in Greater Bandung.